The cosmological constant problem and the effective potential of a gravity-coupled scalar - Ferrero, Renata; Percacci, Roberto (Journal of High Energy Physics, 2024)
We consider a quantum scalar field in a classical (Euclidean) De Sitter background, whose radius is fixed dynamically by Einstein’s equations. In the case of a free scalar, it has been shown by Becker and Reuter that if one regulates the quantum effective action by putting a cutoff N on the modes of the quantum field, the radius is driven dynamically to infinity when N tends to infinity. We show that this result holds also in the case of a self-interacting scalar, both in the symmetric and broken-symmetry phase. Furthermore, when the gravitational background is put on shell, the quantum corrections to the mass and quartic self-coupling are found to be finite.
CRIS-Team Scopus Importer:2024-09-27
Keywords: Cosmological models; Models of Quantum Gravity; Nonperturbative Effects; Renormalization and Regularization